Cytotoxicity Effects and Apoptosis Induction by Bisbenzylisoquinoline Alkaloids from Triclisia subcordata. - Uche, F; Drijfhout, F; McCullagh, J; Richardson, A; Li, W (Wiley, 2016)
Triclisia subcordata Oliv (Menispermeaceae) is a medicinal plant traditionally used for the treatment of various diseases in West Africa. The ethanol extract of T. subcordata and its fractions were screened for in vitro anti-ovarian cancer activities using the Sulforhodamine B assay. The crude alkaloids showed the strongest activity in cell growth assays on Ovcar-8 and A2780 cell lines (IC50  < 2.4 µg/mL). A bisbenzylisoquinoline alkaloid-cycleanine was isolated using HPLC and identified by mass spectrometry and nuclear magnetic resonance analyses. The IC50 values of cycleanine and tetrandrine (an alkaloid previously reported from this plant) ranged from 7 to 14 μM on Ovcar-8, A2780, Ovcar-4, and Igrov-1 ovarian cancer cell lines. The IC50 of cycleanine on human normal ovarian surface epithelial cells was 35 ± 1 μM, hinting at modest selectivity toward cancer cells. Both cycleanine and tetrandrine caused apoptosis as shown by activation of caspases 3/7 and cleavage of poly(ADP-ribose) polymerase to form poly(ADP-ribose) polymerase-1 by using western blot analysis. Flow cytometry analyses showed that the percentages of apoptotic cells and cells in subG1 phase increased after exposure of cycleanine and tetrandrine to Ovcar-8 cells for 48 h compared with control. Cycleanine, like its isomer tetrandrine isolated from T. subcordata, could be a potential new anti-ovarian cancer agent acting through the apoptosis pathway.